2015
DOI: 10.5937/tehnika1501164t
|View full text |Cite
|
Sign up to set email alerts
|

Integrated planning aimed at sustainability city logistics solutions

Abstract: 1. UVOD Rast problema realizacije robnih tokova i pritisak javnosti od kraja prošlog veka podstakli su interesovanje za oblast city logistike (CL). Zapravo, porasla je svest i briga o uticaju logističkih aktivnosti na ekonomsku, ekološku i društvenu održivost gradova. Od ovog perioda raste broj istraživanja, formiraju se baze podataka, definišu i testiraju različite inicijative i koncepcijska rešenja.[1] U cilju dobijanja relevantnih podataka i pregleda stanja, od kraja prošlog veka realizovano je nekoliko vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The solutions are defined according to typical CL solutions and their combination with the technologies of Industry 4.0. The ongoing phenomenon in CL is the increase of small delivery frequencies [50], which cause most of the problems in the planning and realisation of logistics activities [6,7]. This trend tends to continue in the future, therefore the focus of this article is set on such categories of goods flows.…”
Section: Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions are defined according to typical CL solutions and their combination with the technologies of Industry 4.0. The ongoing phenomenon in CL is the increase of small delivery frequencies [50], which cause most of the problems in the planning and realisation of logistics activities [6,7]. This trend tends to continue in the future, therefore the focus of this article is set on such categories of goods flows.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Attempts to implement individual initiatives and measures in practice have shown that the traditional approach for CL planning is unsustainable [6]. Aside from the understanding of city characteristics, identification of participants, their demands, goals and interactions, successful implementation of CL solutions requires integrated planning, cooperation of stakeholders, removing of all barriers and defining of measures that would support the realisation of plans [7]. The application of modern Industry 4.0 technologies makes the definition of creative and sustainable CL solutions possible.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem is the lack of planning activities and encompassing, long-term CL policies and practices [12]. Instead of treating logistics as a service to the local economy, local authorities have, in most cases, an antagonistic attitude towards the realization of logistics activities, especially transportation.…”
Section: Logistics Sustainability Problems At a Micro-levelmentioning
confidence: 99%
“…For solving CL problems, it is important to consi der the opinions, goals, and interests of all stakeholder groupslogistics service providers, service users, local residents, and local authorities [15]. The relationships among those stakeholders are complex, with often conflicting goals [12]. The goal for logistics service providers is in the reduction of costs and the increase of profit of providing logistics services.…”
Section: Stakeholders Criteria and Concepts Of CLmentioning
confidence: 99%
“…the consequences for the entire system of the city logistics should be considered. However, changes in the problem solving approaches and integrated planning require a certain level of understanding of the nature of logistics activities, which is usually not the case (Tadić and Zečević, 2015).…”
Section: Introductionmentioning
confidence: 99%